Optimization of conjugated polymer blend concentration for high performance organic solar cells - Xu, C.; Wright, M.; Elumalai, Naveen Kumar; Mahmud, M.; Gonçales, V.; Upama, M.; Uddin, A. (2018)
Recently, conjugated polymer poly[(5,6-difluoro-2,1,3-benzothiadiazol-4,7-diyl)-alt-(3,3′′′-di(2-octyldodecyl)-2,2′;5′,2″;5″,2′′′-quaterthiophen-5,5′′′-diy)] (PffBT4T-2OD), gained immense attention among the researchers for the photovoltaic device—owing to high temperature processability, high crystallinity and superior charge transport characteristics. In addition, PffBT4T-2OD displays a unique aggregation property which plays a crucial role in determining the quality of the photoactive blend film and concomitantly influencing the organic photovoltaic (OPV) device performance substantially. Here we demonstrate the detailed investigation into the mechanisms governing the aggregation properties of PffBT4T-2OD:PC71BM blend and its role in determining the interfacial properties—material and electronic; together influencing the device performance as a whole. Spectroscopic analysis (XRD and FTIR) indicate that increasing the blend composition influences the aggregation properties in the film, as a function of increased side chain and polymer backbone interactions. Contact angle measurements showed that this, in turn, greatly influences the wettability of the photoactive layer with the adjacent electron transporting layer (ETL) surface. Impedance spectroscopy measurements revealed that the modified surface properties significantly result in the variation of charge transport characteristics across the ETL/polymer interface. The OPV devices employing the optimized blend concentration 33 mg/ml with favourable aggregation properties exhibits high power conversion efficiency of about 9.6% which is 45% higher than the reference device. A detailed relationship between the aggregation characteristics and the related variation in the interfacial properties is correlated with the device performance.